1999
DOI: 10.1002/hep.510290333
|View full text |Cite
|
Sign up to set email alerts
|

Control of the Tissue Inhibitor of Metalloproteinases–1 Promoter in Culture–Activated Rat Hepatic Stellate Cells: Regulation by Activator Protein–1 Dna Binding Proteins

Abstract: In the injured liver hepatic stellate cells (HSCs) undergo a dramatic phenotypic transformation known as ''activation'' in which they become myofibroblast-like and express high levels of the tissue inhibitor of metalloproteinase 1 (TIMP-1). HSC activation is accompanied by transactivation of the TIMP-1 promoter. Truncation mutagenesis studies delineated a minimal active promoter consisting of nucleotides ؊102 to ؉60 relative to the major start site for transcription. Removal of an AP-1 site located at nucleoti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
100
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 78 publications
(105 citation statements)
references
References 33 publications
5
100
0
Order By: Relevance
“…Although TIMP-1 promoter contains activator protein-1 binding site (31), inhibition of activator protein-1 does not always lead to TIMP-1 down-regulation. For example, in hepatic stellate cells, induction of c-Fos and c-Jun is unlikely to result in transactivation of the TIMP-1 promoter (32). Therefore, it is suggested that unidentified factors may be involved in the regulation of TIMP-1 expression (32 -34).…”
Section: Discussionmentioning
confidence: 99%
“…Although TIMP-1 promoter contains activator protein-1 binding site (31), inhibition of activator protein-1 does not always lead to TIMP-1 down-regulation. For example, in hepatic stellate cells, induction of c-Fos and c-Jun is unlikely to result in transactivation of the TIMP-1 promoter (32). Therefore, it is suggested that unidentified factors may be involved in the regulation of TIMP-1 expression (32 -34).…”
Section: Discussionmentioning
confidence: 99%
“…Primary rodent HSCs were isolated and maintained as previously described. [3][4][5][6][7] The LX-2 line was described elsewhere. 7 (L)-JNKI1, a cell-permeable peptide inhibitor of JNKs, SP600125 SAPK inhibitor II, and MAPKK inhibitor PD98059 were purchased from Calbiochem.…”
Section: Isolation and Culture Of Quiescent And Activatedmentioning
confidence: 99%
“…3 TIMP-1 gene transcription is induced during culture activation of isolated HSCs and is under the control of regulatory elements in the TIMP-1 promoter including activator protein-1 (AP-1) and RUNX binding sites. [4][5][6][7] …”
mentioning
confidence: 99%
See 2 more Smart Citations